Report of the 3rd Joint Australia-Japan Workshop 'Australia and Japan collaboration in Antarctic Science' - Kawaguchi, S; Watanabe, K (National Institute of Polar Research, 2016)
The 3rd Joint Workshop on Australian and Japanese Collaboration inAntarctic Science was held at the Institute for Marine and Antarctic Studies, University ofTasmania, Hobart, Australia on the 6th and 7th of August 2015. The primary aim of theworkshop was to identify and highlight current collaborations and campaigns, and thoseplanned for the next few years, and to share this information to maximize the synergy andopportunities for East Antarctic science within the international context. Discussioncovered a range of issues including research areas of common interest, resource sharing,development of joint research proposals, multinational research coordination, and futuremeetings.